Sistema de gerência de informação de processos industriais via Web - Souza, Alessandro José de (2005)
The structure of Industrial Automation bases on a hierarchical pyramid, where restricted information islands are created. Those information islands are characterized by systems where hardware and software used are proprietors. In other words, they are supplied for just a manufacturer, doing with that customer is entailed to that supplier. That solution causes great damages to companies. Once the connection and integration with other equipments, that are not of own supplier, it is very complicated. Several times it is impossible of being accomplished, because of high cost of solution or for technical incompatibility. This work consists to specify and to implement the visualization module via Web of GERINF. GERINF is a FINEP/CTPetro project that has the objective of developing a software for information management in industrial processes. GERINF is divided in three modules: visualization via Web, compress and storage and communication module. Are presented results of the utilization of a proposed system to information management of a Natural Gas collected Unit of Guamar´e on the PETROBRAS UN-RNCE.